BIOM-37. EVALUATION OF TEMPORALIS MUSCLE THICKNESS WITH TOXICITY AND SURVIVAL IN GLIOBLASTOMA PATIENTS RECEIVING CHEMORADIATION. (14th November 2022) - Saraf, Anurag; Hill, Cameron; Youssef, Gilbert; Christ, Sebastian; Tanguturi, Shyam; McFaline-Figueroa, J Ricardo; Chukwueke, Ugonma; Lee, Eudocia; Reardon, David A; Arnaout, Omar; Bi, Wenya Linda; Haas-Kogan, Daphne; et al.
Abstract: BACKGROUND: Treatment-related toxicity is common in patients with glioblastoma (GBM) receiving chemotherapy and radiotherapy (RT). Temporalis muscle thickness (TMT) is a biomarker associated with sarcopenia and worse clinical outcomes in GBM, however its relation to treatment toxicity is less studied. We hypothesize that TMT may predict toxicity and survival in GBM patients. METHODS: We reviewed consecutive patients with IDH-wildtype GBM treated from 2014-2019 at a single academic center. TMT was retrospectively assessed on T1-weighted MRI scans and dichotomized based upon previously validated sex-specific cutoff values. TMT was measured on baseline MRI scan at time of diagnosis. Cox regression multivariable analysis (MVA) was used to assess survival. RESULTS: We evaluated 351 patients with median age of 60y (range 20-94) and median follow-up of 14mo. Most patients were male (59%), baseline KPS >70 (95%), and MGMT unmethylated (55%). After maximal safe resection, most patients received standard (90%) or hypofractionated (10%) RT with concurrent systemic therapy (89%). On MVA, baseline low TMT (HR 1.93, p=0.01), age >65y, baseline KPS, and MGMT-unmethylated status were associated with worse OS. On MVA, baseline low TMT (HR 1.95, p=0.01), age >65y, MGMT-unmethylated status, and discontinuing systemic therapy were associated with worse profession-free survival (PFS). 21 patients did not complete anticipated treatment course of chemoradiation and adjuvant systemic therapy due to toxicity, primarily thrombocytopenia, associated with worse OS on MVA (HR 1.99, p< 0.01). Low TMT was associated with higher risk of stopping treatment due to adverse events (OR 5.25, p< 0.01) independent of age, sex, extent of resection, RT dose on MVA. CONCLUSION: Baseline low TMT was associated with worse PFS and OS, and it was associated with treatment interruption due to treatment toxicity in GBM patients. While further validation is needed, TMT may help identify patients who will benefit from aggressive symptom management or treatment deintensification.